Benefiting from the Digital Economy : Cambodia Policy Note - Beschorner, Natasha; Neumann, James; Sanchez Martin, Miguel Eduardo; Larson, Bradley (World Bank, Washington, DC, 2018)
While Cambodia has achieved stellar growth and poverty reduction over the last two decades, the next wave of growth is anticipated to come from increasing value-added as well as nurturing new sectors such as the Digital Economy. Over the past two decades, facilitated by preferential trade treatment and strong foreign direct investment inflows, growth and job creation have been taking place in activities with relatively limited value added, such as garment manufacturing, rice cropping, and construction. In recent years, Cambodian authorities have issued several policy documents relevant to digital development. Overall, the objectives and high-level program goals are generally consistent with international good practice, and envisage partnerships between the Government and the private sector at multiple levels. The Rectangular Strategy Phase III 2013-2018 highlights the need to further develop e-Government and encourage the private sector to invest in technology. This was followed in 2014 by the approval of the Cambodia ICT Master Plan 2020 which aims to improve ICT industry and human resources development, internet connectivity, cybersecurity, and government e-services—and in 2016 by the Telecoms and ICT Policy which outlines policy measures and associated targets to expand ICT infrastructure and develop ICT human capacity. In addition, a draft Cambodia e-Government Master Plan 2017-2022 has been drafted, although not yet adopted. The draft outlines programs to provide quality information and digital services, in collaboration with prospective beneficiaries; connect with people on public policies and decisions, in particular through social media; and increase government efficiency by establishing basic foundations for digital government (e.g. cloud, enterprise architecture, intensive staff capacity building) and a government portal on which ministries can host their services. Numerous institutions across Government are tasked with the implementation of these policies and strategies. This policy note responds to a request from the Royal Government of Cambodia for the World Bank to assess the current state of its Digital Economy and identify policies to further develop it.The Policy Note applies the analytical framework presented in the World Bank’s World Development Report 2016: Digital Dividends, to identify challenges and suitable policy options, and it is intended to inform the preparation of the upcoming Rectangular Strategy Phase IV (2018—2023).